PERAN NILAI PELANGGAN DALAM MEMEDIASI HUBUNGAN STRATEGI PEMASARAN TERHADAP KINERJA PEMASARAN (STUDI KASUS PADA PETANI KARET DI KECAMATAN SENTAJO RAYA, KABUPATEN KUANTAN (JURNAL AGRIBISNIS TERPADU, 2022)
This study aims to analyze the effect of market strategy and marketing mix strategy on marketing performance mediated by customer value. The study was conducted on smallholder rubber farmers in Sentajo Raya District, Kuantan Singingi Regency, Riau Province with a total sample of 36 respondents selected by random sampling. The types of data used in this research are primary data and secondary data. The data analysis tool used in this research is SmartPLS 3.0 Sobel test and VAF calculation. The results of this study indicate that market strategy and marketing mix strategy have a significant effect on customer value, market strategy and marketing mix strategy have no significant effect on marketing performance, customer value has a significant effect on marketing performance, and market strategy through customer value has no significant effect on marketing performance. Meanwhile, the marketing mix strategy through customer value has a significant effect on marketing performance where the role of the mediating effect on customer value is partial mediation of 0.540 or 54.0%.